Culture and Characterization of Microglia from the Adult Murine Retina - Gayathri Devarajan; Mei Chen; Elizabeth Muckersie; Heping Xu (The Scientific World Journal)
Purpose. To develop a protocol for isolating and culturing murine adult retinal microglia and to characterize the phenotype and function of the cultured cells. Method. Retinal single-cell suspensions were prepared from adult MF1 mice. Culture conditions including culture medium, growth factors, seeding cell density, and purification of microglia from the mixed cultures were optimised. Cultured retinal microglial cells were phenotyped using the surface markers CD45, CD11b, and F4/80. Their ability to secrete proinflammatory cytokines in response to lipopolysaccharide (LPS) stimulation was examined using cytometric bead array (CBA) assay. Results. Higher yield was obtained when retinal single-cell suspension was cultured at the density of 0.75×106 cells per cm2 in Dulbecco’s modified Eagle medium (DMEM)/F12 + Glutamax supplement with 20% fetal calf serum (FCS) and 20% L929 supernatant. We identified day 10 to be the optimum day of microglial isolation. Over 98% of the cells isolated were positive for CD45, CD11b, and F4/80. After stimulating with LPS they were able to secrete proinflammatory cytokines such as IL-6 and TNF-α and express CD86, CD40, and MHC-II. Conclusion. We have developed a simple method for isolating and culturing retinal microglia from adult mice.